RESTRICTIONS ON FREEDOM OF EXPRESSION IN INDONESIA FROM A HUMAN RIGHTS PERSPECTIVE - Lusty Shine La Juwi; Andi Pangerang Moenta; Hamzah Halim (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
This research is focused on the concept of limiting freedom of speech applied in Indonesia and its comparison with restrictions on freedom of expression applied in liberal countries, namely the United States and Germany. Aiming to maintain public order in society, the restrictions are not carried out arbitrarily because they must be in accordance with laws and regulations and moral values, decency and other general values in society and aim to protect the basic rights of others. This research is normative legal research. The results of the study are, First, a comparison of restrictions on freedom between countries that adhere to liberalism (the United States and Germany) and the State of Indonesia found that there are differences in terms of regulation, where America does not include restrictions on the right to freedom of expression in its constitution but only based on jurisprudence, whereas Indonesia and Germany include arrangements for limiting the right to freedom of speech in their respective constitutions. This is because not all countries can adhere to the universal concept of human rights. Second, the forms of restrictions on freedom of opinion are regulated in laws and regulations, including in Article 28 J paragraph (2) of the 1945 Constitution of the Republic of Indonesia and Article 73 of Law no. 39 of 1999 concerning Human Rights. Where the restrictions on the right to freedom of opinion implemented in Indonesia are in accordance with these rules and do not violate human rights because the forms of self-imposed restrictions aim to protect the rights and freedoms of others, and to remain based on moral values, decency and public order and restrictions done in the common interest of the nation.